An investigation to identify the factors that cause failure in English essay, precis, and composition papers in CSS exams - Gul, Kiran (2024)
The research study aims to examine why candidates in Pakistan failed the English Essay, Precis, and Composition sections of the Central Superior Services (CSS) tests. Those candidates chosen for various civil service positions take the prestigious and difficult CSS exam. The study aims to discover candidates’ difficulties in these particular CSS exam sections and investigate methods for enhancing their English language ability. A mixed-methods strategy is used in the research process to collect both quantitative and qualitative data. Participants in the CSS exam who once took the English Essay, Precis, and Composition papers and got fail in it received a survey form to respond according to their experience. Other than this, we also conducted semi-structured interviews with CSS test winners currently working as officials, such as Deputy Commissioners, Assistant Commissioners, Assistant Superintendents of Police, and Deputy Superintendents of Police. Insights into the causes of failure and the experiences of successful candidates are sought after from both data sources. The research findings highlighted several key factors contributing to failure in English Essays, Precis, and Composition papers. These factors include lack of comprehension and understanding, grammatical errors, inadequate organization, poor handwriting, insufficient practice, lack of originality, difficulty in adapting to essay prompts and precis passages, poor organization, failure to understand and address the purpose, insufficient development of ideas, failure to reach the required word count, grammatical mistakes, neglecting proofreading and revision, poor writing expression, and weak induction and conclusion in essays, tough paper pattern old formatted curriculum. Participants reported struggling to express their ideas coherently, having limited language skills, facing challenges in managing time effectively, lacking proper precis structure understanding, inadequate expertise in the subject, lack of training and resources, lack of analytical and critical thinking abilities, inadequate exam preparation, time management issues, poor grammar abilities, exam phobia, and limited vocabulary as potential factors contributing to failure.